2021
DOI: 10.1021/acs.orglett.1c02099
|View full text |Cite
|
Sign up to set email alerts
|

Cascade aza-Wittig/6π-Electrocyclization in the Synthesis of 1,6-Dihydropyridines

Abstract: A metal-free protocol for the synthesis of substituted 1,6-dihydropyridines with quaternary stereogenic centers via a cascade aza-Wittig/6π-electrocyclization process has been developed. The high functional group compatibility and broad scope of this method were demonstrated by using a wide range of easily available vinyliminophosphoranes and ketones, with yields up to 97%. A modification of the obtained products allowed for an increase in complexity and chemical diversity. Finally, attempts for asymmetric syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…It is important to note that the cis-configuration of the central double bond of an acyclic hexatriene is difficult to achieve, which is a fundamental requirement for this cyclization process. [30] We found that introducing an electron-withdrawing carbonyl group at the C5 position of hexatrienes can maintain the required cis-configuration of the central C4-C5 double bond. In our case, s1 m can generate 2 m' and 2 m'q, via respective transition states T1 m and T1mq (see SI-36-01 for details).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…It is important to note that the cis-configuration of the central double bond of an acyclic hexatriene is difficult to achieve, which is a fundamental requirement for this cyclization process. [30] We found that introducing an electron-withdrawing carbonyl group at the C5 position of hexatrienes can maintain the required cis-configuration of the central C4-C5 double bond. In our case, s1 m can generate 2 m' and 2 m'q, via respective transition states T1 m and T1mq (see SI-36-01 for details).…”
Section: Resultsmentioning
confidence: 85%
“…The initial phase of the reaction sequence commences from s1 m , i. e., the “cyclization‐reactive” s‐cis conformer of 1 m under the experimental conditions. It is important to note that the cis ‐configuration of the central double bond of an acyclic hexatriene is difficult to achieve, which is a fundamental requirement for this cyclization process [30] . We found that introducing an electron‐withdrawing carbonyl group at the C5 position of hexatrienes can maintain the required cis ‐configuration of the central C4‐C5 double bond.…”
Section: Resultsmentioning
confidence: 86%
“…The sequences of Passerini reactions, followed by post-condensation reactions, constitute useful synthetic methods in the preparation of structurally diverse heterocyclic compounds [24][25][26][27][28][29]. The aza-Wittig reaction has also been utilized widely in preparation of various heterocycles under mild neutral conditions [30][31][32]. Recently we have reported the synthesis of 3H-2-benzoxepin-1-ones, 4H-3,1-benzoxazines and oxazoles by combination of a Passerini with an intramolecular aza-Wittig reaction [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of electrocyclic reactions for the synthesis of heterocyclic compounds involves serious challenges due to the limited synthetic availability of azapolyenes of the required structure. Whereas 1-azabuta-1,3-dienes are readily available from a condensation of unsaturated carbonyl compounds with primary amines [13][14][15], the methods for the synthesis of their isomers, 2-azabuta-1,3-dienes, which include the Mannich olefination of alkylidene glycinates [16], the Wittig reaction of N-(diphenylmethylidene)oxamate [17], the coupling of imines with activated acetylenes [18], and the aza-Wittig reaction of Nvinylphosphazenes [19][20][21][22][23] are more complicated and allow the introduction of only a limited set of substituents. In recent years, another convergent approach to azapolyenes 6 and 9 based on the ring opening of three-and five-membered heterocycles 1 and 2 under the action of transition metal carbenes 3 has been intensively developed (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%